Fine Scale Characterization of Shale Reservoirs Methods and Challenges - Ostadhassan, Mehdi (SpringerBriefs in Petroleum Geoscience & Engineering, 2018)
This book summarizes the authors' extensive experience and interdisciplinary approach to demonstrate how acquiring and integrating data using a variety of analytical equipment can provide better insights into unconventional shale reservoir rocks and their constituent components. It focuses on a wide range of properties of unconventional shale reservoirs, discussing the use of conventional and new analytical methods for detailed measurements of mechanical properties of both organic and inorganic constituent elements as well as of the geochemical characteristics of organic components and their origins. It also addresses the investigation of porosity, pore size and type from several perspectives to help us to define unconventional shale formation. All of these analyses are treated individually, but brought together to present the rock sample on a macro scale. This book is of interest to researchers and graduate students from various disciplines, such as petroleum, civil, and mechanical engineering, as well as from geoscience, geology, geochemistry and geophysics. The methods and approaches can be further extended to biology and medicine.